Establishing causal links between aquatic biodiversity and ecosystem functioning: status and research needs - Daam, Michiel A. (2019)
Understanding how changes in biodiversity affects ecosystem functioning is imperative in allowing Ecosystem-Based Management (EBM), especially when addressing global change and environmental degradation. Research into the link between biodiversity and ecosystem functioning (BEF) has indeed increased considerably over the past decades. BEF research has focussed on terrestrial ecosystems and aquatic ecosystems have received considerably less attention. Due to differences in phylogenetic diversity, ecological processes and reported BEF relationships, however, it may at least be questionable whether BEF relationships are exchangeable between these ecosystems (i.e. terrestrial and aquatic). The aim of the present paper was therefore to pinpoint key areas and bottlenecks in establishing BEF relationships for aquatic ecosystems (freshwater, transitional, and marine). To this end, the available literature with special emphasis on the last 10 years was assessed to evaluate: i) reported mechanisms and shapes of aquatic BEF relationships; ii) to what extent BEF relations are interchangeable or ecosystem-specific; and iii) contemporary gaps and needs in aquatic BEF research. Based on our analysis, it may be concluded that despite considerable progress in BEF research over the past decades, several bottlenecks still need to be tackled, namely incorporating the multitude of functions supported by ecosystems, functional distinctiveness of rare species, multitrophic interactions and spatial-temporal scales, before BEF relationships can be used in ecosystem-based management.